Venoms as an adjunctive therapy for Parkinson’s disease: where are we now and where are we going? - Gazerani, Parisa (Future Sci OA, 2020)
Neurodegenerative diseases, including Parkinson’s disease (PD), are increasing in the aging population. Crucially, neurodegeneration of dopaminergic neurons in PD is associated with chronic inflammation and glial activation. Besides this, bradykinesia, resting tremor, rigidity, sensory alteration, and cognitive and psychiatric impairments are also present in PD. Currently, no pharmacologically effective treatment alters the progression of the disease. Discovery and development of new treatment strategies remains a focus for ongoing investigations. For example, one approach is cell therapy to prevent dopaminergic neuronal loss or to slow PD progression. The neuroprotective role of a diverse range of natural products, including venoms from bees, scorpions, snakes and lizards, are also being tested in preclinical PD models and in humans. The main findings from recent studies that have investigated venoms as therapeutic options for PD are summarized in this special report.